Development Of Personalized Marketing in The Era of Big Data (Open Herald: Periodical of Methodical Research, 2024)
Personalized marketing has emerged as a critical strategy for businesses to engage with consumers in a highly competitive and digitally driven marketplace. With the proliferation of big data technologies, businesses have unprecedented access to vast amounts of consumer data, enabling them to create tailored marketing experiences that resonate with individual preferences and behaviors. This article examines the development of personalized marketing in the era of big data, exploring the opportunities and challenges it presents for businesses. By analyzing case studies and industry trends, this article provides insights into the effective implementation of personalized marketing strategies and offers practical recommendations for businesses looking to leverage big data to enhance customer engagement and drive revenue growth